SIRT1: The first key to unlocking the mystery of cardiovascular diseases - Dinislam, Khuzin; Khoso, Muneer Ahmed; Kataev, Valeriy A.; Meshcheryakova, Svetlana; Liu, Heng; Liu, Ling; Guo, Madi; Wang, Song; Lou, Han; Zhang, Yong; Liu, Xin (Frontiers in Pharmacology, 2026)
Cardiovascular disease, (CVD) the leading cause of death worldwide, encompasses various heart and vascular disorders that significantly elevate morbidity and mortality rates. Sirtuin 1 (SIRT1), a NAD+ dependent deacetylase, plays a key role in cardiovascular health and pathology by regulating fundamental processes such as endothelial function, oxidative stress, inflammation, senescence, metabolism, cardiac hypertrophy, and heart failure. Through these mechanisms, SIRT1 emerges as critical factor in the pathophysiology of CVDs, including heart failure, atherosclerosis, hypertension, and myocardial infarction. SIRT1 modulates several cellular pathways to regulate complex cellular processes associated with cardiovascular disorders. This review summarizes recent findings regarding the physiological and pathological roles of SIRT1 related to heart diseases and explores the therapeutic potential of targeting SIRT1 and sirtuin family members for CVD treatment.